Undergoing an immunization is effortlessly, manageable or difficult according to five‐year‐old children. Issue 2 (30th June 2014) - Harder, Maria; Christensson, Kyllike; Söderbäck, Maja
<x xml:space="preserve">Abstract</x> Background To prevent diseases among children they regularly undergo immunizations. Previous research show different approaches available to facilitate immunization‐procedures for children to protect them from harm. To complement this research and provide care suited for children, research recognizing their perceptions of undergoing such a procedure is needed. Aim The aim of this study was to describe 5‐year‐old children's perceptions of undergoing an immunization. Method A phenomenographic approach and analysis was used to describe the children's (n = 21) various perceptions. The data‐collection was accomplished directly after the immunization to grasp the children's immediate perceptions. Drawings and reflective talks were used as they are considered as suitable methods when involving young children in research. The right to conduct research with children was approved by the appropriate research ethics committee and also by each child and the parents. Results The findings show that children's perceptions of an immunization‐procedure may vary from effortlessly, to manageable or difficult. Regardless of how the child perceive the immunization‐procedure each perception embrace the children's descriptions of actors and articles in the situation, their feelings in the situation and also their actions to deal with the immunization. Nevertheless, these descriptions vary according to how the children perceive the immunization as effortlessly, manageable or difficult. Conclusion Children's and adults' perceptions of medical procedures may differ and children need guidance, time and space to deal with them. Recognizing children's perceptions of undergoing an immunization contributes to the promotion of their right to be involved in their own health care and towards the development of child‐centred care.